PADAT POPULASI DAN INTENSITAS SERANGAN HAMA WALANG SANGIT (Leptocorisa Acuta Thunb.) PADA TANAMAN PADI SAWAH DI KABUPATEN MINAHASA TENGGARA - Rivo Manopo; Christina L. Salaki; Juliet E.M. Mamahit; Emmy Senewe (COCOS, 2013)
ABSTRACTPaddy is the most important staple food in Indonesia, since more than half of the population is dependent on the rice that the paddy plants produce. About 1,75 billion of the three billion Asians, including 210 million Indonesians rely on rice as their primary source of calories. The object of this research is to know the population density and infestation intensity of the paddy bug L. acuta on paddy plants in the North Tombatu, East Tombatu and Pasan Districts of the South-east Minahasa Regency. This research is expected to inform about the population density and infestation intensity of the paddy bug L. acuta in several different places and attempts in controlling it. Results of this research show that the paddy bug has spread in paddy fields over the three districts. The highest population was found in the district of East Tombatu (33,9 individuals / ten double sweeps), followed by the Pasan District (24,1 individuals / ten double sweeps), while the district of North Tombatu had the lowest population (9,2 individuals / ten double sweeps). The high paddy bug population is influenced by environmental factors and farmers’ habits in breeding field paddy plants. The intensity of the paddy bug infestation is already high, so the presence of this pest is highly worrisome.Key words : paddy plants, population density and infestation intensity, paddy bug pest (Leptocorisa acuta Thunb.)